Bedside surgery in the newborn infants: survey of the Italian society of pediatric surgery - Gloria Pelizzo; Pietro Bagolan; Francesco Morini; Mariagrazia Aceti; Daniele Alberti; Mario Andermarcher; Luigi Avolio; Fabio Bartoli; Vito Briganti; Sebastiano Cacciaguerra; Francesco S. Camoglio; Pierluca Ceccarelli; et al. (Italian Journal of Pediatrics, 2020)
Abstract Introduction This is the report of the first official survey from the Italian Society of Pediatric Surgery (ISPS) to appraise the distribution and organization of bedside surgery in the neonatal intensive care units (NICU) in Italy. Methods A questionnaire requesting general data, staff data and workload data of the centers was developed and sent by means of an online cloud-based software instrument to all Italian pediatric surgery Units. Results The survey was answered by 34 (65%) out of 52 centers. NICU bedside surgery is reported in 81.8% of the pediatric surgery centers. A lower prevalence of bedside surgical practice in the NICU was reported for Southern Italy and the islands than for Northern Italy and Central Italy (Southern <Northern<Central, p < 0.03). The most frequent clinical characteristics of neonates was preterm neonates with birthweight < 1200 g, with cardiorespiratory instability and/or ventilatory dependence. The most frequently selected indications to surgery were pneumothorax, pleural effusion, pericardial effusion, central venous catheter (CVC) positioning, intestinal perforation, patent ductus arteriosus ligation and congenital diaphragmatic hernia. More than 60% of respondents report no institutional recommendations and dedicated informed consent on bedside surgical procedures. The lack of dedicated areas and infrastructures is considered a relative contraindication to the performance of bedside surgery. Conclusion Bedside surgery is performed in the majority of the Italian pediatric surgery centers included in this census. The introduction of a national set of surgery guidelines would be widely welcomed.